Phenomenological Reading of Vasily Sesemann’s Philosophy - Gutauskas, Mintautas (Problemos, 2018)
[text in Lithuanian] Review of: Dalius Jonkus. Vosyliaus Sezemano filosofija: savęs pažinimo ir estetinės patirties fenomenologija. [Philosophy of Vasily Sesemann: Phenomenology of Self-Awareness and Aestetic Experience], in Lithuanian. Kaunas: Vytauto Didžiojo universitetas, Versus Aureus. Summary in English. – 192 p. ISBN 9786094671869